2010
DOI: 10.1590/s0034-737x2010000100014
|View full text |Cite
|
Sign up to set email alerts
|

Consumo, digestibilidade e estimativa do valor energético de alguns volumosos por meio da composição química

Abstract: Intake, digestibility and energetic value estimates of feedstuff through chemical compositionNutrient intake, apparent digestibility and total digestible nutrients (TDN) levels of sugar cane, elephant grass silage, corn silage and sorghum silage were evaluated in sheep. The TDN values of feeds were also estimated with the equations proposed by NRC (2001). Twenty male castrated rams, housed in individual pens, were distributed in a randomized design in four treatments (feedstuffs) and five repetitions (animals)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 14 publications
0
7
0
8
Order By: Relevance
“…Rocha Júnior et al (2003) found 18.43% digestibility for the NDF of fresh sugarcane and Campos et al (2010) verified greater nutrient intake in diets based on fresh sugarcane silage (NDF = 48.87%). Pontes (2007) verified that the use of calcium oxide did not affect the digestibility of total carbohydrates.…”
Section: Resultsmentioning
confidence: 96%
“…Rocha Júnior et al (2003) found 18.43% digestibility for the NDF of fresh sugarcane and Campos et al (2010) verified greater nutrient intake in diets based on fresh sugarcane silage (NDF = 48.87%). Pontes (2007) verified that the use of calcium oxide did not affect the digestibility of total carbohydrates.…”
Section: Resultsmentioning
confidence: 96%
“…Contenido energético de pastos y ensilajes con la metodología de NRC (2001 (Andrade, 2006;Boga et al, 2014;Boschini-Figueroa, 2006;Campos et al, 2010;Ferro et al, 2013;Giraldo et al, 2006;Villalobos, 2006).…”
Section: Resultados Y Discusiónunclassified
“…Existem componentes que determinam o valor energético dos alimentos utilizados nas dietas de ruminantes como os CNF (Campos, et al, 2015). Neste trabalho, pode-se observar na Tabela 7, que a inclusão da soja reduziu os teores de CNF, quando se compara com a silagem do milho, e isso pode estar associado a menor participação de grão de milho na silagem.…”
Section: Tratamentosunclassified